Penerapan Kearifan Lokal di Bandar Udara Internasional Sam Ratulangi di Manado - Putri Nur Genggona; Kartika Fajar Nieamah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Sam Ratulangi International Airport in Manado plays a strategic role as the main gateway for tourists visiting North Sulawesi, making significant contributions to local tourism and the economy. The implementation of local wisdom at this airport, such as the use of regional languages and the integration of cultural elements in terminal design, aims to enrich the tourist experience and showcase the cultural richness of North Sulawesi. However, challenges remain regarding capacity and service quality, as well as maintaining the authenticity of local culture. This study aims to analyze how the application of local wisdom at Sam Ratulangi International Airport impacts the tourist experience in North Sulawesi and to evaluate the local cultural values implemented at the airport in enhancing the visitor experience. The research design uses a qualitative approach with a case study method to assess the application of local wisdom at Sam Ratulangi International Airport, Manado. The study, conducted in July 2024, combines interviews, observations, and documentation to gather data. Interviews with airport managers, local communities, and passengers provide insights into the impact of local wisdom. Observations focus on cultural elements at the airport, while documentation includes official data and relevant literature. Data validity is tested through triangulation of techniques and sources. Data analysis involves reduction, presentation, and conclusion drawing to address or refine the research problem. The study findings indicate that the application of local wisdom at Sam Ratulangi International Airport, such as traditional Kolintang music, batik exhibitions, and the use of regional languages, enhances the tourist experience by creating a distinctive atmosphere that introduces North Sulawesi's culture. Local values such as